Mobile Health Interventions for Improving Health Outcomes in Childhood: A Scoping Review Protocol. - Palombo, Claudia Nery Teixeira (2022)
Introduction: The use of mobile devices for health care has been increasingly frequent in recent years. Studies show the immense potential of this technology as an instrument to favor the development of personal and social skills, in the sense of acquiring greater control and decision-making power over health care. Aim: The objective of this scoping review is to map the mobile health interventions for improving health outcomes in childhood. Method: This protocol was carried out in according to Joanna Briggs Institute methodology and Preferred checklist Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR), according to the following steps: review question; eligibility criteria (PCC); literature search strategy; study selection; data extraction and data presentation. The review question is: How are mHealth interventions being applied to improve childhood health outcomes (disease prevention, monitoring or diagnosis)? The review will include experimental, quasi-experimental and descriptive observational study designs with quantitative or qualitative approach. Dissertations will be considered, but conference abstracts, posters, editorials, commentaries, and opinion papers will be excluded. The search will be limited to studies published in English, Spanish and Portuguese in the last 10 years. The databases to be searched include PubMed, CINAHL, Embase, Scielo, Web of Science, LILACS, Health System Evidence, and gray literature databases. Results: The result of the selection flow will be presented in the form of tables and figure, according to PRISMA-ScR. Conclusion: This study will provide evidence on the development and implementation of online tools to promote children's health.